Dispersing agent for conductive paste as well as preparation method and application of dispersing agent

By using polyamic acid polymers as dispersants for conductive paste, the dispersion performance of carbon nanotubes is improved by using electrostatic and π-π interaction, the problem of carbon nanotube agglomeration is solved, the performance and life of the battery are improved, and the performance and life of the battery are reduced. The cost.

CN119320498AInactive Publication Date: 2025-01-17SOUTH CHINA UNIV OF TECH +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411462151.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Carbon nanotubes are prone to agglomeration in batteries, resulting in reduced performance. The existing dispersant generally has poor dispersion effects and cannot meet the needs of high-energy density and low-cost batteries.

Method used

Polyamic acid polymers are used as dispersants for conductive paste, and prepared by polymerization reaction, siloxane flexible units and aromatic diamine rigid structure are introduced, and the dispersion performance of carbon nanotubes is improved by electrostatic action and π-π interaction. .

Benefits of technology

It effectively improves the dispersion performance of carbon nanotubes, reduces the risk of thermal runaway in the battery, improves the fluidity and processability of the battery, extends the cycle life of the battery, and reduces the cost of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320498A_ABST
    Figure CN119320498A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of batteries, and particularly discloses a dispersing agent for conductive paste as well as a preparation method and application of the dispersing agent. The dispersing agent for the conductive paste contains a polyamide acid polymer; the polyamide acid polymer is formed by polymerizing raw materials including aromatic dianhydride, aliphatic diamine and aromatic diamine. The dispersing agent for the conductive slurry contains polar functional groups which can be adsorbed on the surface of a conductive agent through electrostatic interaction, meanwhile, the dispersing agent for the conductive slurry and the conductive agent interact and are adsorbed through sigma-pi bonds, and the dispersing performance of the conductive agent is further enhanced. Pi-Pi interaction exists between rigid structures such as aromatic rings and amido bonds in the dispersing agent for the conductive slurry and the conductive agent, so that the agglomeration problem of the conductive agent, especially carbon nanotubes, can be improved, and the dispersion of the conductive agent is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a dispersant for conductive slurry and a preparation method and application thereof. Background Art

[0002] At present, electric vehicles have put forward higher requirements for battery performance, such as higher energy density and lower battery cost. Commonly used carbon black materials can no longer meet the requirements of high energy density and low-cost batteries. Carbon nanotubes (CNTs) have advantages such as excellent conductivity, excellent mechanical properties and high specific surface area. They are expected to improve battery performance and cycle life while meeting the needs of the electric vehicle industry for more advanced and efficient battery technology. CNTs are nanomaterials with excellent performance. Their unique structure and excellent mechanical, electronic and optical properties make them widely used in various fields. However, there are strong van der Waals forces and π-π stacking between CNTs tubes, which are easy to agglomerate and difficult to disperse. After CNTs agglomerate, all performances will be greatly reduced. Therefore, the dispersion problem of CNTs is the primary problem to be solved in order to give full play to its advantages.

[0003] At present, the dispersion of carbon nanotubes is mainly carried out by physical dispersion and chemical dispersion. Physical dispersion is to disperse carbon nanotubes in a solution by means of mechanical stirring or ultrasound. It is a relatively simple and intuitive method, but when the external conditions are restored, the conductive agent particles are easy to re-aggregate. Chemical dispersion is to change the chemical properties of the surface of carbon nanotubes by adding surfactants to improve their dispersibility in solution. Covalent modification in chemical dispersion generally requires surface oxidation of CNTs, which changes the properties of CNTs themselves, while non-covalent modification does not change the properties of CNTs. It uses π-π interactions and van der Waals forces to adsorb, entangle, and wrap dispersant molecules on CNTs. However, the existing dispersants generally have poor dispersion effects on CNTs and cannot meet the requirements of use. Summary of the invention

[0004] In order to overcome the problems existing in the prior art, one of the objectives of the present invention is to provide a dispersant for conductive paste.

[0005] A second object of the present invention is to provide a method for preparing a dispersant for conductive paste.

[0006] A third object of the present invention is to provide a conductive paste.

[0007] A fourth object of the present invention is to provide a lithium ion battery.

[0008] A fifth object of the present invention is to provide the above-mentioned dispersant for conductive paste and / or application of the above-mentioned conductive paste in the field of batteries.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is:

[0010] The first aspect of the present invention provides a dispersant for a conductive paste, wherein the dispersant for a conductive paste contains a polyamic acid polymer (the dispersant for a conductive paste is a polyamic acid polymer); the polyamic acid polymer is polymerized from raw materials including aromatic dianhydride, aliphatic diamine, and aromatic diamine.

[0011] Preferably, the aromatic dianhydride includes at least one of pyromellitic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 4,4'-diphthalic anhydride, 3,3',4,4'-dibenzophenonetetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 3,4'-oxydiphthalic anhydride, and 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride.

[0012] Preferably, the aliphatic diamine includes at least one of 1,2-bis(2-aminoethoxy)ethane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, poly(dimethylsiloxane), and bis(3-aminopropyl) end-capping. The siloxane (DMS) in the aliphatic diamine is composed of Si-O-Si bonds, and its bond angle is large, so that the polyamic acid polymer has excellent flexibility and flexibility, and the high bond energy makes it have good chemical stability and thermal stability. Therefore, the conductive paste dispersant in the present invention introduces a siloxane flexible unit with good heat resistance into the polyamic acid main chain to enhance the high temperature resistance of the molecular chain and improve the solubility of the molecular chain. In addition, by adjusting the content of the siloxane flexible group in the polyamic acid polymer, a polyamic acid polymer with different rigidity and flexibility ratios can be obtained, and then a variety of dispersants with different effects can be obtained.

[0013] Preferably, the aromatic diamine includes at least one of 2,4-diaminobenzoic acid, 3,4-diaminobenzoic acid, 3,5-diaminobenzoic acid, and 2,5-diaminoterephthalic acid. The present invention uses an aromatic diamine containing a carboxyl group to provide a rigid benzene ring structure for the conductive paste dispersant, thereby enhancing the mechanical stability and thermal stability of the conductive paste dispersant.

[0014] Preferably, the ratio of the total amount of the aliphatic diamine and the aromatic diamine to the amount of the aromatic dianhydride is 1:(1-1.3).

[0015] Preferably, based on the total mole percentage of the aliphatic diamine and the aromatic diamine being 100%, the mole percentage of the aliphatic diamine is 50%-90%.

[0016] The second aspect of the present invention provides a method for preparing the dispersant for conductive paste provided in the first aspect of the present invention, comprising the following steps:

[0017] The conductive paste dispersant is prepared by polymerizing raw materials including aromatic dianhydride, aliphatic diamine and aromatic diamine.

[0018] Preferably, the polymerization reaction temperature is 10-50°C.

[0019] Preferably, the polymerization reaction time is 4 to 24 hours.

[0020] Preferably, the polymerization step is carried out under an inert atmosphere.

[0021] Preferably, the inert atmosphere is selected from at least one of nitrogen and argon.

[0022] Preferably, the polymerization reaction is carried out in the presence of a solvent.

[0023] Preferably, the solvent for the polymerization reaction is an organic solvent.

[0024] Preferably, the solvent for the polymerization reaction includes at least one of N-methylpyrrolidone, N,N-dimethylacetamide and dimethylformamide.

[0025] Preferably, the preparation method further comprises a step of centrifugation after alcohol precipitation; the step of centrifugation after alcohol precipitation is located after the polymerization reaction step.

[0026] Preferably, the alcohol precipitation step uses ethanol as solvent.

[0027] The third aspect of the present invention provides a conductive paste, comprising a dispersant for conductive paste, a conductive agent, and a solvent; the mass ratio of the dispersant for conductive paste to the conductive agent is (0-100):100, but not 0.

[0028] Preferably, the conductive agent comprises carbon nanotubes.

[0029] Preferably, the conductive agent further comprises at least one carbon-based conductive material selected from acetylene black, superconducting carbon black, graphene, and Ketjen black.

[0030] A fourth aspect of the present invention provides a lithium-ion battery, comprising an electrolyte; the electrolyte contains the dispersant for the conductive paste according to the first aspect of the present invention or the conductive paste according to the third aspect of the present invention.

[0031] The fifth aspect of the present invention provides use of the dispersant for conductive paste according to the first aspect of the present invention and / or the conductive paste according to the third aspect of the present invention in the field of batteries.

[0032] The beneficial effects of the present invention are as follows: the conductive paste dispersant of the present invention contains polar functional groups, which can be adsorbed on the surface of the conductive agent through electrostatic action, and at the same time, the conductive paste dispersant interacts and adsorbs with the conductive agent through σ-π bonds, further enhancing the dispersibility of the conductive agent. Rigid structures such as aromatic rings and amide bonds in the conductive paste dispersant have π-π interactions with the conductive agent, which can improve the agglomeration problem of the conductive agent, especially carbon nanotubes, and achieve dispersion of the conductive agent.

[0033] The conductive paste of the present invention contains polyamic acid polymers, which not only can make the conductive paste have good fluidity and processability, but also can reduce the risk of thermal runaway of the battery containing the conductive paste. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a photo of the carbon nanotube mixed solution containing the dispersant for conductive paste in Example 1 after being left to stand for 30 days.

[0035] Figure 2 This is a photo of the carbon nanotube mixed solution containing the dispersant for conductive paste in Examples 2 to 3 after being left to stand for 30 days.

[0036] Figure 3 It is the absorbance test graph of the carbon nanotube solution and the polyamic acid solution of different concentrations in the embodiment.

[0037] Figure 4 This is a standard curve diagram drawn according to the Lambert-Beer law in an embodiment of the present invention.

[0038] Figure 5 This is a test diagram of the dispersion effect of the carbon nanotube dispersion on the carbon nanotubes in Examples 4 to 6 and Comparative Example 1. DETAILED DESCRIPTION

[0039] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0040] Example 1

[0041] This example provides a dispersant for a conductive paste for lithium-ion batteries, which is polyamic acid (PMDA-DMS-DABA-7:3PAA) and is prepared by a preparation method comprising the following steps:

[0042] Preparation of polyamic acid (PMDA-DMS-DABA-7:3PAA): 14mmol of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (NH2-DMS) and 6mmol of diamine monomer of 3,5-diaminobenzoic acid (DABA) were dissolved in 60mL of N-methylpyrrolidone (NMP), and nitrogen was continuously introduced. After stirring for 30 minutes under an ice-water bath to dissolve it, 20.4mmol of dianhydride monomer pyromellitic anhydride (PMDA) was added in batches, and nitrogen was introduced in a vacuum for 4 hours to obtain a polyamic acid polymer solution. After the reaction is completed, the solution after the reaction is poured into a large amount of ethanol to precipitate, and the obtained precipitate is centrifuged and vacuum dried for 12 hours to obtain a polyamic acid solid powder.

[0043] Example 2

[0044] This example provides a dispersant for a conductive paste for lithium-ion batteries, which is polyamic acid (PMDA-DMS-DABA-8:2PAA) and is prepared by a preparation method comprising the following steps:

[0045] Preparation of polyamic acid (PMDA-DMS-DABA-8:2PAA): 16mmol of 1,3-bis(3-aminopropyl)tetramethyldisiloxane and 4mmol of diamine monomer of 3,5-diaminobenzoic acid were dissolved in 60mL of N-methylpyrrolidone, and nitrogen was continuously introduced. After stirring for 30 minutes under an ice-water bath to dissolve it, 20.4mmol of dianhydride monomer pyromellitic anhydride was added in batches, and nitrogen was introduced in a vacuum for 4 hours to obtain a polyamic acid polymer solution. After the reaction was completed, the solution after the reaction was poured into a large amount of ethanol to precipitate, and the obtained precipitate was centrifuged and vacuum dried for 12 hours to obtain a polyamic acid solid powder.

[0046] Example 3

[0047] This example provides a dispersant for a conductive paste for lithium-ion batteries, which is polyamic acid (PMDA-DMS-DABA-9:1PAA) and is prepared by a preparation method comprising the following steps:

[0048] Preparation of polyamic acid (PMDA-DMS-DABA-9:1PAA): 18 mmol of 1,3-bis(3-aminopropyl)tetramethyldisiloxane and 2 mmol of diamine monomer of 3,5-diaminobenzoic acid were dissolved in 60 mL of N-methylpyrrolidone, and nitrogen was continuously introduced. After stirring for 30 minutes under an ice-water bath to dissolve it, 20.4 mmol of dianhydride monomer pyromellitic anhydride was added in batches, and nitrogen was introduced in a vacuum for 4 hours to obtain a polyamic acid polymer solution. After the reaction was completed, the solution after the reaction was poured into a large amount of ethanol to precipitate, and the obtained precipitate was centrifuged and vacuum dried for 12 hours to obtain a polyamic acid solid powder.

[0049] The reaction formula of the polyamic acid in Examples 1 to 3 is as follows:

[0050]

[0051]

[0052] Example 4

[0053] This example provides a carbon nanotube dispersion, which is prepared by the following preparation method:

[0054] 10 mg of the polyamic acid (PMDA-DMS-DABA-7:3PAA) in Example 1, 10 mg of carbon nanotubes and 10 mL of NMP were weighed, mixed and ultrasonicated for 2 hours to prepare the carbon nanotube dispersion in this example.

[0055] Example 5

[0056] This example provides a carbon nanotube dispersion, which is prepared by the following preparation method:

[0057] 10 mg of the polyamic acid (PMDA-DMS-DABA-8:2PAA) in Example 2, 10 mg of carbon nanotubes and 10 mL of NMP were weighed, mixed and ultrasonicated for 2 hours to prepare the carbon nanotube dispersion in this example.

[0058] Example 6

[0059] This example provides a carbon nanotube dispersion, which is prepared by the following preparation method:

[0060] 10 mg of the polyamic acid (PMDA-DMS-DABA-9:1PAA) in Example 3, 10 mg of carbon nanotubes and 10 mL of NMP were weighed, mixed and ultrasonicated for 2 hours to prepare the carbon nanotube dispersion in this example.

[0061] Comparative Example 1

[0062] This example provides a carbon nanotube dispersion, which is prepared by the following preparation method:

[0063] 10 mg of carbon nanotubes and 10 mL of NMP were weighed, mixed and ultrasonicated for 2 hours to prepare the carbon nanotube dispersion in this example.

[0064] Performance Testing:

[0065] The polyamic acid (0 mg, 0.8 mg, 4 mg, 8 mg) prepared in Examples 1 to 3 was added to a 0.8 mg / mL carbon nanotube NMP mixed solution, the NMP solution was 10 mL, and after uniform mixing, ultrasonication was performed and allowed to stand for two hours to obtain a polyamic acid / carbon nanotube composite solution, wherein the mass percentage of polyamic acid (based on CNTs) was 0%, 10%, 50%, and 100%, respectively. In addition, a 0.8 mg / mL (without carbon nanotubes) polyamic acid NMP mixed solution was prepared. The above-prepared solutions were then allowed to stand for 30 days, and the actual pictures after standing were as follows: Figure 1 and Figure 2 As shown, Figure 1 In the figure (a), from left to right are the physical pictures of the polyamic acid / carbon nanotube composite solution and the polyamic acid NMP mixed solution in Example 1 with polyamic acid concentrations of 10%, 50%, and 100%, respectively. Figure 1 Figure (b) is a physical picture of the carbon nanotube composite solution in Example 1 with a polyamic acid concentration of 0% (ie, without polyamic acid). Figure 2 In the figure (a), from left to right are the actual pictures of the polyamic acid / carbon nanotube composite solution and the polyamic acid NMP mixed solution with polyamic acid concentrations of 10%, 50%, and 100% in Example 2. Figure 2 In the figure (b), from left to right, there are physical pictures of the polyamic acid / carbon nanotube composite solution and the polyamic acid NMP mixed solution with polyamic acid concentrations of 10%, 50%, and 100% in Example 3.

[0066] Depend on Figure 1 and Figure 2 It can be seen that after adding different contents of PMDA-DMS-DABA polyamic acid dispersant of the present invention, no obvious sedimentation phenomenon occurred after 30 days of standing. In contrast, the pure CNTs solution containing only carbon nanotubes showed obvious sedimentation. This shows that the siloxane polyamic acid precursor has a good dispersing effect on carbon nanotubes, mainly due to the adsorption formed by the interaction between siloxane and carbon nanotubes through the σ-π bond. At the same time, the conjugated structure present in the polyamic acid precursor interacts with the CNTs surface by π-π, so that it remains suspended without sedimentation. In addition, -COOH and -NH- in PAA form hydrogen bonds with the oxygen-containing functional groups in CNTs, and the combined action of these chemical bonds improves the dispersion effect of CNTs in the solution.

[0067] Then, the Lambert-Beer law method was used to determine the dispersion ability of the polymer on the carbon nanotubes. The specific test method is as follows:

[0068] S1, UV spectrum test of polymer. Prepare NMP solution of polyamic acid (0.8 mg / mL) prepared in Examples 1 to 3, and then test the UV spectrum of NMP solution of polyamic acid prepared in Examples 1 to 3 in the range of 200-800 nm, as shown in detail. Figure 3 As shown in (b), Figure 3 (b) It can be seen that the characteristic absorption peak of the polymer is between 200-400nm. In order to eliminate the influence of the characteristic absorption peak of the polymer on the carbon nanotube test, the ultraviolet measurement range of the carbon nanotube concentration is selected outside the polymer absorption band, which is selected as 500nm.

[0069] S2, measuring the ultraviolet absorption spectra of carbon nanotubes of different concentrations. 4 mg, 8 mg, 12 mg, 18 mg, and 20 mg of carbon nanotubes were respectively placed in 1 L of NMP, and then ultrasonically treated for 2 hours to prepare NMP solutions of carbon nanotubes with concentrations of 4 mg / L, 8 mg / L, 12 mg / L, 18 mg / L, and 20 mg / L, and then the ultraviolet spectra of the NMP solutions of carbon nanotubes of different concentrations in the range of 300-800 nm were tested, as shown in detail. Figure 3 As shown in (a), Figure 3 (a) It can be seen that as the concentration of carbon nanotubes increases, the ultraviolet absorption intensity increases accordingly. According to the Lambert-Beer law, the absorbance measured at 500nm and the carbon nanotube concentration are paired and a standard curve is drawn, as shown in the following figure. Figure 4 As shown, the standard curve is: y = 0.00873 × x-0.01368. After fitting, the correlation coefficient R 2 It is 0.99064, which shows that there is a good linear relationship between carbon nanotube concentration and absorbance, which conforms to the Lambert-Beer law.

[0070] S3, the polyamic acid prepared in Examples 1 to 3 is selected and mixed with carbon nanotubes and NMP at a concentration of 10 mg:10 mg:10 mL, and the carbon nanotube dispersions in Examples 4 to 6 are obtained after ultrasonic treatment for 2 hours, and then the ultraviolet absorbance of the carbon nanotube dispersions in Examples 4 to 6 and Comparative Example 1 at 500 nm is tested, and then the concentration corresponding to the horizontal axis is found on the standard curve, which is the dispersion ability of the polymer on the carbon nanotubes. The results measured according to the above test method are as follows: Figure 5 As shown. Figure 5It can be seen that the dispersion concentrations of carbon nanotubes in the carbon nanotube dispersions in Examples 4 to 6 and Comparative Example 1 are 11 mg / L, 6 mg / L, 8 mg / L, and 5 mg / L, respectively. It can be seen that compared with pure NMP, the dispersion of carbon nanotubes is enhanced after adding the polyamic acid dispersant. Among them, PMDA-DMS-DABA-7:3 polyamic acid has better dispersibility. This is because the rigid diamine content contained therein is higher, which promotes the π-π interaction between the polymer and the carbon nanotubes, so the dispersion ability is stronger.

[0071] In summary: the dispersant for the conductive paste for lithium ion batteries in the present invention does not need to match a special pulping process during use. It can achieve a better dispersion effect on carbon nanotubes by adding it in proportion on the basis of the existing pulping process, without additional process costs, and can effectively reduce the risk of secondary aggregation of particles, improve the fluidity of the carbon nanotube dispersion, reduce the resistance of the pole piece, and increase the capacity of the battery. In addition, the carbonyl group contained in the dispersant for the conductive paste in the present invention has a good affinity with the electrolyte, and is used in lithium ion batteries to increase the diffusion rate of lithium ions. The polar functional groups in the PI (polyimide) molecular chain are adsorbed on the surface of the conductive agent through electrostatic action. At the same time, the siloxane polymer and the conductive agent form adsorption through the interaction of σ-π bonds, which further enhances the dispersion performance. The polyamic acid conductive paste dispersant contains hydrophilic groups and lipophilic groups, which form an effective steric hindrance and inhibit the sedimentation of carbon nanotube particles. The polar functional groups carboxyl and amino groups are hydrophilic groups, while siloxane exhibits lipophilic properties. From the perspective of the microscopic interface, hydrophilic groups and lipophilic groups can effectively reduce the surface tension of the solid-liquid interface, improve the wetting and penetration properties, increase the solid content of active substances and the ease of coating, and are conducive to the uniform dispersion of slurry particles, thereby improving battery performance.

[0072] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A dispersant for conductive paste, characterized in that: The conductive paste dispersant contains a polyamic acid polymer; the polyamic acid polymer is polymerized from one or more raw materials including aromatic dianhydride, aliphatic diamine and aromatic diamine.

2. The dispersant for conductive paste according to claim 1, characterized in that: The aromatic dianhydride includes one or more of pyromellitic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 4,4'-diphthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 3,4'-oxydiphthalic anhydride, and 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride; The aliphatic diamine includes one or more of 1,2-bis(2-aminoethoxy)ethane, 1,3-bis(3-aminopropyl)tetramethyldisiloxane, poly(dimethylsiloxane), and bis(3-aminopropyl) end-capping; The aromatic diamine includes one or more of 2,4-diaminobenzoic acid, 3,4-diaminobenzoic acid, 3,5-diaminobenzoic acid, and 2,5-diaminoterephthalic acid.

3. The dispersant for conductive paste according to claim 1, characterized in that: When the polyamic acid polymer is polymerized from aromatic dianhydride, aliphatic diamine and aromatic diamine, the ratio of the total amount of the aliphatic diamine and the aromatic diamine to the amount of the aromatic dianhydride is 1:(1-1.3).

4. The dispersant for conductive paste according to claim 3, characterized in that: Taking the total mole percentage of the aliphatic diamine and the aromatic diamine as 100%, the mole percentage of the aliphatic diamine is 50%-90%.

5. The method for preparing a dispersant for conductive paste according to any one of claims 1 to 4, characterized in that: The following steps are involved: The conductive paste dispersant is prepared by polymerizing raw materials including aromatic dianhydride, aliphatic diamine and aromatic diamine.

6. The method for preparing a dispersant for conductive paste according to claim 5, characterized in that: The polymerization reaction temperature is 10°C to 50°C, and the polymerization reaction time is 4 to 24 hours; And / or, the preparation method further comprises a step of centrifugation after alcohol precipitation; the step of centrifugation after alcohol precipitation is located after the polymerization reaction step.

7. A conductive paste, characterized in that: The conductive paste comprises the dispersant for conductive paste according to any one of claims 1 to 4, a conductive agent and a solvent; the mass ratio of the dispersant for conductive paste to the conductive agent is (0 to 100):100, but not 0.

8. The conductive paste according to claim 7, characterized in that: The conductive agent includes carbon nanotubes; Alternatively, the conductive agent includes carbon nanotubes and at least one carbon-based conductive material selected from acetylene black, superconducting carbon black, graphene, and Ketjen black.

9. A lithium ion battery, characterized in that: The invention comprises an electrolyte; the electrolyte contains the dispersant for conductive paste according to any one of claims 1 to 4 or the conductive paste according to any one of claims 7 to 8.

10. Use of the dispersant for conductive paste according to any one of claims 1 to 4 and / or the conductive paste according to any one of claims 7 to 8 in the field of batteries.

Citation Information

Patent Citations

  • Carbon nanotube dispersing agent for dispersing carbon nanotubes and preparation method and application of carbon nanotube dispersing agent

    CN109867776A

  • Self-repairing polyimide and application thereof in lithium ion battery

    CN118271630A

  • Carbon nanotube dispersant including polyamic acid

    JP2013036021A